2013
DOI: 10.1159/000356690
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Peritoneal Disseminated Angiosarcoma 20 Years after Ovarian Cancer Diagnosis

Abstract: Angiosarcoma is a rare form of sarcoma which may be either a primary tumor or it may result from previous irradiation because of another tumor. In this paper, we present a case of a female patient diagnosed as having peritoneal disseminated angiosarcoma 20 years after ovarian cancer treatment (surgery, chemotherapy and radiotherapy). The case was very atypical because of an extremely rare peritoneal location and disseminated nature of the changes. Based on the initial histological picture, poorly differentiate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…While the initial results led to 85 publications, after the screening process, only 20 publications met the inclusion criteria (Figure 1). Overall, six retrospective,17–22 two population-based cohort,23 24 and 12 case reports25–36 were included. Key characteristics of the analyzed population are summarized in Online Supplemental Tables 2 and 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the initial results led to 85 publications, after the screening process, only 20 publications met the inclusion criteria (Figure 1). Overall, six retrospective,17–22 two population-based cohort,23 24 and 12 case reports25–36 were included. Key characteristics of the analyzed population are summarized in Online Supplemental Tables 2 and 3.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the clinical data on survival were not always described, as highlighted in Online Supplemental Table 3. Data on overall survival were available in 11 studies19 20 22 25–27 31–34 36 and ranged between 7 and 57 months. Only three articles reported data on progression-free survival on angiosarcomas that ranged between 1 month and 3 years for bones, soft tissue and/or local progression after treatment 26 32 34.…”
Section: Resultsmentioning
confidence: 99%
“…One such case report was of disseminated peritoneal angiosarcoma that occurred 20 years after treatment for ovarian cancer with RT 9. Other such case reports include that of small bowel angiosarcoma and greater omentum angiosarcoma 7 10.…”
Section: Discussionmentioning
confidence: 99%
“…All cases presented with advanced disease, which were complicated with massive hemorrhagic ascites and peritoneal dissemination. While the cases receiving palliative care described the rapidly progressing character of the disease ( 3 , 5 ), Chudecha-Glaz et al reported the achievement of partial response by platinum-based chemotherapy, which lead to cytoreductive surgery and control of the disease at least temporarily ( 4 ). Swiftly making the diagnosis and enabling chemotherapy administration seems to be the key in controling the disease.…”
Section: Discussionmentioning
confidence: 99%